Leaves of White Beetroot As a New Source of Antioxidant and Anti-Inflammatory Compounds - Urszula Gawlik-Dziki (Plants, 2020)
The white beetroot cv. Śnieżna Kula is the first betanin-free beetroot registered in the European Union. The aim of this study was to compare the phenolic acids profile and antioxidant capacity of leaves of white (SK) and red (CC) beetroots and red (LC) and white (BL) Swiss chard growing in Poland. LC leaves were the richest source of total phenolics (16.55 mg GAE/g FW) and phenolic acids (1.81 mg/g FW), while the highest content of flavonoids was determined in CC leaves (1.6 mg QE/g FW). The highest antiradical activity was observed for LC, whereas CC extract exhibited the highest chelating power. BL and CC leaf extracts demonstrated high LOX inhibitory potential (EC50 = 53.23 and 56.97 mg FW/mL, respectively). An uncompetitive type of LOX inhibition was obtained for all extracts. SK extracts demonstrated the highest XO inhibitory activity (EC50 = 81.04 mg FW/mL). A noncompetitive type of XO inhibition was obtained in both extracts from red leaves (CC and LC), whereas an uncompetitive mode of inhibition was observed in the case of white leaf (SK and LC) extracts. Thus, it can be assumed that the presence of betanin influences the XO inhibition mechanism.